Pengaruh Gaya Kepemimpinan terhadap Motivasi Kerja Karyawan Departemen Housekeeping di Hotel A Ubud - Ni Putu Diah Sri Maharani; I Gusti Ayu Putu Wita Indrayani; Ni Desak Made Santi Diwyarthi (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2021)
The competition in this industry has become extremely tight as the number of star and non-star hotels in Bali increased in 2019, reaching 4,323 hotels. The goal of this study was to examine the impact of the leadership style on the work motivation of employees in the Hotel A Ubud's Housekeeping Department. The participants in this study were all employees of the Hotel A Ubud's Housekeeping Department. In this study, a saturated sample or census technique was used for sampling. In this study, simple regression analysis was used for data analysis. The analysis results show that leadership style has a positive and significant effect on employee work motivation. As a result, the better the application of a leadership style in a company, the higher the work motivation. The findings of this study have implications for the development of hotel policies aimed at increasing employee work motivation by paying attention to the leader's style and character while leading his subordinates. However, it is expected that future research will examine the effect of these two variables on a broader scope using a longitudinal approach, so that the research results can be generalized.